The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1242/jcs.137281
|View full text |Cite
|
Sign up to set email alerts
|

RNAi screen identifies KIF15 as a novel regulator of integrin endocytic trafficking

Abstract: ABSTRACTa2b1 integrin is one of the most important collagen-binding receptors, and it has been implicated in numerous thrombotic and immune diseases. a2b1 integrin is a potent tumour suppressor, and its downregulation is associated with increased metastasis and poor prognosis in breast cancer. Currently, very little is known about the mechanism that regulates the cell-surface expression and trafficking of a2b1 integrin. Here, using a quantitative fluorescence-microscopybased RNAi assay, we investigated the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 141 publications
0
24
0
Order By: Relevance
“…Drechsler et al reported that KIF15 is a second tetrameric spindle motor (in addition to kinesin-5, Eg5) and reported the mechanisms by which hKIF15 and its inhibitor hTpx2 modulate spindle microtubule architecture (Tanenbaum et al , 2009; Drechsler et al , 2014; Eskova et al , 2014). The motor domain structure of KIF15 was captured in the ‘ATP-like’ configuration, with the neck linker docked onto the catalytic core.…”
Section: Discussionmentioning
confidence: 99%
“…Drechsler et al reported that KIF15 is a second tetrameric spindle motor (in addition to kinesin-5, Eg5) and reported the mechanisms by which hKIF15 and its inhibitor hTpx2 modulate spindle microtubule architecture (Tanenbaum et al , 2009; Drechsler et al , 2014; Eskova et al , 2014). The motor domain structure of KIF15 was captured in the ‘ATP-like’ configuration, with the neck linker docked onto the catalytic core.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, tail retraction leads to loss of cell polarity and re-establishment of a new cell axis (Theisen et al, 2012). KIF15, another kinesin motor, was recently identified in a fluorescence-microscopy-based RNA interference screen as a new regulator of inactive α2β1 integrin traffic (Eskova et al, 2014). However, unlike KIF1C, KIF15 promotes α2β1 integrin endocytosis through the transport of Dab2 to the plasma membrane to engage the α2 integrin tail (Fig.…”
Section: The Cell Cytoskeleton and Integrin Trafficmentioning
confidence: 99%
“…Another microtubule-dependent motor protein which was recently identified in a screen for regulators of a2 integrin endocytosis is the kinesin KIF15 [80]. Depletion of KIF15 inhibited the intracellular accumulation of a2 integrin, which is likely due to the fact that it also induced a loss of plasma membrane-associated Dab2, as Dab2 depletion mimicked KIF15 depletion [80].…”
Section: Integrin Traffickingmentioning
confidence: 99%